2012
DOI: 10.5539/ijbm.v7n17p34
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Markets Commerce: The Role of Country-of-Origin and Animosity in Purchase Intention

Abstract: At present, firms must face interrelated challenges in global marketing, such as the increased consumer market internationalization and the rapid growth of emerging markets economy. In this context, the purpose of this study is to differentiate between cognitive and affective components of the country-of-origin (reputation of firms from a country-of-origin and animosity) and frame them as antecedents of trust and purchase intention. The study supports the view that the reputation of firms from the country-of-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 42 publications
(65 reference statements)
0
17
0
1
Order By: Relevance
“…Moreover, various authors have suggested that consumers' perceptions of, and associations with, the country of origin are often influenced by the reputation (with regard to various attributes) of the country in question (e.g. Chen et al, 2011;Insch and McBride, 1998;Insch and McBride, 2004;Jiménez and Martin, 2012;Li and Wyer, 1994;Lim and O'Cass, 2001;Michaelis et al, 2008;Verlegh and Steenkamp, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, various authors have suggested that consumers' perceptions of, and associations with, the country of origin are often influenced by the reputation (with regard to various attributes) of the country in question (e.g. Chen et al, 2011;Insch and McBride, 1998;Insch and McBride, 2004;Jiménez and Martin, 2012;Li and Wyer, 1994;Lim and O'Cass, 2001;Michaelis et al, 2008;Verlegh and Steenkamp, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, the country of origin information leads to better brand familiarity and thus, enhanced customer brand relationships. Jiménez and Martín (2012) confirmed that country of origin information works as a safeguard transaction to establish successful brand relationships.…”
mentioning
confidence: 50%
“…For instance, certain scholars (Michaelis, Woisetschläger, Backhaus, & Ahlert, 2008;Tam, 2008) considered country-of-origin as one of the important factors that influence customers' behaviour and guide firms toward maintaining valuable relationships with them. Similarly, Jiménez and Martín (2012) emphasized that country of origin information works as a safeguard transaction to build superior brand relationships. Particularly, the reputation of brands originating from a certain country becomes a key measure of available offer and also a basis in establishing trust-based relationships over time (Jiménez & Martín, 2012;Nijssen & Herk, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Past research on animosity toward a country maintained that nature and the content of the concept is pure affective as referring a feeling, emotion of dislike, anger, defiance, hostility, antipathy, rejection with regard to people, customs, ideas, or products from that country (Jung et al, 2002;Jiménez & Martín, 2012). However, although there is not a prominent classification as cognitive and affective animosity, recent studies conceptualize animosity as an attitude comprising emotion and belief components (Klein et al, 1998;Jung et al, 2002;Leong et al, 2008).…”
Section: Consumer Animositymentioning
confidence: 99%